The overemphasis on `talent` in parasport development - Howe, D.; Silva, C. F.; Moreira de Almeida, R. (Talent development in Paralympic sport: Researcher and practitioner perspectives, 2022)
It takes years and years of hard work to produce an Olympic champion. In the case of Paralympic sport, the route for developing a champion is often not as long or as unpredictable for a number of reasons. First of all, people who experience disability are less likely to be physically active in comparison to those who are considered able because of multiple impediments to participation. Related to this, not many individuals who possess Paralympic eligible bodies are physically active globally. In this chapter we start our examination by providing a brief background of the Paralympic movement before turning our attention toward the task of finding and developing Paralympic sport talent in contemporary contexts. Our attention then shifts to the value of talent transfer within Paralympic sport and we close the chapter by discussing the whole process of talent identification and the impact that it can have upon the Paralympic sport practice community.